Open economy macroeconomics - Rødseth, Asbjørn (Cambridge University Press, 2000)
Professor Rodseth provides a broad survey of open economy macroeconomics within a unified framework. This upper-level textbook reviews the theories employed by ministries of finance, central banks and financial institutions which form the basis for most quantitative models of open economies. It also points out the limitations of these theories and gives an update on recent research. The emphasis is on how the nature of the markets for foreign exchange and for exports and imports sets the stage for government policy and determines the macroeconomic effects of external and internal shocks. Particular attention is paid to the relations between short- and long-run equilibria and the long-run consequences of national policies. Short-run wage rigidities play a key role, and models with wage bargaining are compared to more traditional formulations. Exchange rate policy and the transmission of shocks are discussed both from a national and an international perspective.